Representative Sector Modeling and Waterflooding Performance in Rumaila Oilfield - Shamkhi, Mustafa Kamil; Aljawad, Mohammed Salih (Iraqi Journal of Science, 2021)
Rumaila supergiant oilfield, located in Southern Iraq has a huge footprint and is considered as the second largest oilfield in the world. It contains many productive reservoirs, some known but without produced zones, and significant exploration potential. A fault divides the field into two domes to the north and south. Mishrif reservoir is the main producing reservoir in the North Rumaila oilfield. It has been producing for more than 40 years and is under depletion. However, it was subjected to water injection processes in 2015, which assisted in recovery and pressure support. Thus, requirements of managing flooding strategies and water-cut limitations are necessary in the next stages of the field life. In this paper, sector modeling was applied to a specific portion of the field, rather than full-field modeling, to accelerate history matching strategy and correlate static to dynamic models’ efficiently, with a minimum level of tolerance. The sector was modeled by surrounding with additional grid blocks and two pseudo wells to achieve a good matching with actual available data. PVT data were used for fluid modeling of a well contained in the sector, and two rock functions were inserted to the model to achieve acceptable history matching. Twelve wells were considered in this research, two of them were injectors and the remaining are producers. For future performance, some of these wells were subjected to new completion and workover processes for field development and pressure maintenance. The importance of the development plan is to represent a way for field development without new wells to be drilled. This was conducted by adding perforations to some wells, plugging the high water-cut production zones, changing production and injection rates, and converting the producers to injectors.